Surface controlled synthesis of Cu2FeSnS4 particles for enhanced hydrogen evolution reaction. (11th October 2021) - Mukurala, Nagaraju; Mokurala, Krishnaiah; Mohapatra, Lokanath; Suman, Siddhartha; Kushwaha, Ajay Kumar
Abstract: Cu2 FeSnS4 (CFTS) particles are synthesized using different surfactants such as thioglycolic acid (TGA), polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA) via the solution process. The effect of surfactants on crystal structure, morphology, elemental composition, and electrocatalytic properties of CFTS particles are investigated. CFTS particles with a better crystalline phase are obtained in PVP (surfactant), while impurity phases are observed in TGA and PVA (surfactants). The morphology of CFTS is significantly changed when a different surfactant is used in the synthesis process. The mixture of aggregate and porous (1 μm) particles is observed when PVA is used as a surfactant to synthesize CFTS particles. At the same time, highly porous particles having nanosheets and nanoparticles at the surface are obtained in the case of PVP. In the TGA case, spherical particles with 1 μm size are observed. The electrocatalytic ability of all CFTS particles toward hydrogen evolution reactions (HER) is studied in 0.5 M H2 SO4 electrolyte. The overpotential of PVP-based CFTS particles is the lowest as ƞ = 421 mV at 10 mA/cm 2 compared to the other two samples. CFTS particles synthesized using PVP exhibit enhanced electro-catalytic performance due to higher surface area. Graphical abstract: Image 1 Highlights: Role of different surfactants on solvothermally grown CFTS particles is examined. Surfactant's control CFTS morphology leads to aggregate, porous, and spherical. Surface-controlled CFTS particles act as electro-catalytic materials for HER. CFTS-PVP-based catalyst exhibits a higher electro-catalyst performance for HER. Structural & morphological stability of recovered CFTS-PVP catalyst is investigated.